The Copyright Ownership Status of Visual Works Generated by Artificial Intelligence - Raiwella, G.P.; Paramyta, Dwi Sartika; Nasution, M.Y.F. Hafidz (Universitas Islam Negeri Sumatera Utara, 2025)
AI has transformed the way humans interact with computer systems, capable of processing complex data and generating new content such as high-quality images. Generative AI (GAI) creates content through descriptive commands, but it presents legal challenges, especially in copyright. The 2014 Copyright Law is unclear in regulating AI-generated works, creating uncertainty about copyright ownership and originality. This research analyzes legal gaps and provides recommendations regarding the copyright ownership status of generative AI works. This study uses a normative legal method with a legal framework approach to analyze relevant regulations. Legal sources are divided into three categories: primary (laws and regulations), secondary (doctrines, scholarly articles), and tertiary (legal dictionaries). Legal materials are collected through library research for further analysis, followed by systematic selection and classification, then analyzed to draw conclusions. Intellectual Property in Indonesia regulates copyrights on works, including those generated by AI. Although AI can create works, it challenges the human creation definition in Law No. 28 of 2014. Legal challenges arise regarding who holds the copyright: the developer, the user, or the AI, requiring a more adaptive legal framework to accommodate works generated by this technology. This research highlights copyright challenges in Indonesia related to AI works that do not meet originality and creativity criteria. There is a need for the development of an adaptive legal framework to protect intellectual property and encourage innovation. This issue requires in-depth approaches from various disciplines to align the law with advancements in digital technology.